The crossing - Paulsen, Gary (New York : Scholastic, 2006)
Thirteen-year-old Manny, a street kid fighting for survival in a Mexican border town, develops a strange friendship with an emotionally disturbed American soldier who decides to help him get across the border.
Keywords: Survival -- Homelessness; Adventure